Pendekatan Transformational Change Pasca Penyetaraan Jabatan Administrasi Ke Dalam Jabatan Fungsional di Ditjen Bina Pembangunan Daerah - Wicaksono, Aldi Gumuruh; Nadia, Fiona Niska Dinda; Fitriani, Tri Ivatul; Rahman, Abdul (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
Bureaucratic simplification in Indonesia is carried out to overcome the problem of a fat and hierarchical bureaucratic structure, which hampers the efficiency and effectiveness of public services. One of the strategic steps taken is to equalize echelon III and IV administrative positions into functional positions in accordance with Permenpan RB Number 17 of 2021. This study aims to analyze the impact of organizational changes after equalizing administrative positions into functional positions at the Directorate General of Regional Development using the Transformational Change approach. The research method used is a qualitative approach with a case study design, utilizing primary data through in-depth interviews and direct observation, as well as secondary data from policy documents and academic literature. The results showed that this policy succeeded in creating a leaner organizational structure and accelerating decision-making. However, the implementation of this policy also presents a number of challenges, such as the mismatch of tasks and functions of functional officials, organizational culture resistance, and limited human resource competencies. In addition, although the work process has shifted from a hierarchical system to collaboration-based work, this transition has not been fully optimized due to technical constraints and lack of training. In conclusion, the Transformational Change approach can be an effective framework to support bureaucratic reform, provided that training, competency development, and technological support and adaptive leadership are strengthened. With the right strategy, the Directorate General of Regional Development can become a model for successful bureaucratic reform at the national level.